(Dis)connectivities in wartime: The therapeutic geographies of Iraqi healthcare–seeking in Lebanon. Issue 3 (4th March 2018) - Dewachi, Omar; Rizk, Anthony; Singh, Neil V.
ABSTRACT: The proliferation of conflicts across borders of Middle Eastern States has transformed the landscapes of health and healthcare across the region. In the case of Iraq, state healthcare has collapsed under the strain of protracted conflicts. Meanwhile, Lebanon's post-war healthcare system is booming, and becoming more privatised. In this paper, we build on an ethnographic study on the movements and experiences of Iraqi patients in Lebanon to show how one of the consequences of war is the rise of alternative forms of healthcare–seeking practices and survival strategies – a therapeutic geography that is embedded in regional economies and geopolitical relations and reconfigurations. We argue for the need to reimagine the disconnectivity and connectivity of healthcare systems under war and conflict as grounded in the empirical realities and experiences of mobility in the Middle East.